The Blackwell companion to religious ethics - Schweiker, William (Malden Blackwell Pub., 2005)
This resource includes detailed discussions of issues in moral theory, offers extensive treatment of the world's major religious traditions and compares the way religions provide resources for addressing current moral challenges.
Keywords: Religious ethics. Morale religieuse. Ethiek. Godsdienst. Ethik Religion